2019
DOI: 10.1016/j.celrep.2019.04.065
|View full text |Cite
|
Sign up to set email alerts
|

Partial Cone Loss Triggers Synapse-Specific Remodeling and Spatial Receptive Field Rearrangements in a Mature Retinal Circuit

Abstract: SUMMARY Resilience of neural circuits has been observed in the persistence of function despite neuronal loss. In vision, acuity and sensitivity can be retained after 50% loss of cones. While neurons in the cortex can remodel after input loss, the contributions of cell-type-specific circuits to resilience are unknown. Here, we study the effects of partial cone loss in mature mouse retina where cell types and connections are known. At first-order synapses, bipolar cell dendrites remodel and synaptic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 55 publications
(78 reference statements)
6
64
0
Order By: Relevance
“…Our findings did not support either of these hypotheses, and it appears that the potentiation of the ERG b-wave is not mediated by disinhibition or altered gap junctional coupling in P23H mice. Hypothesis 1 would align well with recent studies showing that cone bipolar cell dendrites formed new synapses with surviving cones after ~50% of cones had been ablated in juvenile or mature mice ( Care et al, 2019 ; Shen et al, 2020 ). In another study, ablation of 50–90% of rod bipolar cells during development led to an extension of the dendrites of the remaining rod bipolar cells so that they contacted more rods ( Johnson et al, 2017 ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our findings did not support either of these hypotheses, and it appears that the potentiation of the ERG b-wave is not mediated by disinhibition or altered gap junctional coupling in P23H mice. Hypothesis 1 would align well with recent studies showing that cone bipolar cell dendrites formed new synapses with surviving cones after ~50% of cones had been ablated in juvenile or mature mice ( Care et al, 2019 ; Shen et al, 2020 ). In another study, ablation of 50–90% of rod bipolar cells during development led to an extension of the dendrites of the remaining rod bipolar cells so that they contacted more rods ( Johnson et al, 2017 ).…”
Section: Discussionsupporting
confidence: 86%
“…Recent studies using the specific deletion of ~50–90% of rods, cones or rod bipolar cells during development or in mature mice have revealed homeostatic mechanisms associated with the maintenance of normal retinal output and vision ( Care et al, 2020 ; Care et al, 2019 ; Johnson et al, 2017 ; Shen et al, 2020 ; Tien et al, 2017 ). Here we used a P23H knock-in mouse model of RP that recapitulates the human disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study on partial cone loss revealed that inhibitory surrounds of A ON-S ganglion cells expanded, while excitatory centers of these same cells shrank, indicating not only that the inhibitory surround is affected by partial cone loss, but that it may also be a site of compensation for input loss ( Care et al, 2019 ). In contrast to these findings, the present study demonstrates the inhibitory circuits onto ganglion cells remain relatively stable.…”
Section: Discussionmentioning
confidence: 98%
“…Studies concerning synaptic specificity in the OPL are emerging in aging and degenerative disease models. For example, studies on homeostatic remodeling mechanisms following PR death provide particular insight into the etiology and progression of diseases such as age‐related macular degeneration (Care et al, 2019; Dunn, 2015). In the retinas of old mice, for example, HC and BC neurites aberrantly extend into the ONL where they form ectopic synapses.…”
Section: Synaptic Specificity In the Outer Plexiform Layermentioning
confidence: 99%